Leitura e escrita no contexto da alfabetização crítica proposta por Paulo Freire: estudo de caso no município de Embu das Artes - Souza, Edilene de Oliveira Francisco (2013)
Literacy is a topic that is constantly present on the agenda of teacher training programs, in election campaigns, in political speeches and academics. There are many publications that deal with the theme, and each new publication, new questions, new methodologies and new hypotheses arise in trying to find solutions to address the difficulties faced by schools in teaching reading and writing. Aiming point out ways to improve the process of teaching and learning of reading and writing, this research, based on the political and epistemological assumptions proposed by Paulo Freire, indicates possible paths to achieving literacy practices critical and significant. This study is part of a broader research developed in Paulo Freire Chair of the Pontifical Catholic University of São Paulo, coordinated by Professor Dr. Ana Maria Saul, who investigates the presence of referential freireanos in Brazilian education. The town of Embu das Artes was chosen in this research to investigate how assumptions about critical literacy freireanos materialize in policy and practice curriculum this school system. The results demonstrate the possibility of reinventing the thought of Paulo Freire, the floor of the school, in the context of critical literacy